3n-4n+9=-2

Simple and best practice solution for 3n-4n+9=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3n-4n+9=-2 equation:


Simplifying
3n + -4n + 9 = -2

Reorder the terms:
9 + 3n + -4n = -2

Combine like terms: 3n + -4n = -1n
9 + -1n = -2

Solving
9 + -1n = -2

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -1n = -2 + -9

Combine like terms: 9 + -9 = 0
0 + -1n = -2 + -9
-1n = -2 + -9

Combine like terms: -2 + -9 = -11
-1n = -11

Divide each side by '-1'.
n = 11

Simplifying
n = 11

See similar equations:

| -3/4=3-1/2n | | 0.42n-7=5 | | 1=v+8/5 | | 446=q-(235+925) | | N+x=27 | | a+(-27)=(-15) | | 12.88-0.88(x+0.5)=0.25+2(x-3.17) | | 4x+5y+6x-3x+3y= | | https://content.grantham.edu/at/MA105/exams/w2_10.jpg | | 4=60 | | 7+4x=7x+40 | | 2k+-1=2+k | | X^4+11=35 | | 18+7x-9=-27+3x | | -10=(1/4)(8y-12) | | -1x+0.33=0.25 | | 50b+36c= | | x+12=-(13) | | 50b+3c= | | 9+3(3x+5)=24+9x | | 50b+3= | | 60/p=4;15,16,17 | | 1/2x5/4 | | 2(14)-x+8=0 | | x/-7=(-5) | | -5x+13=-15 | | z+2=z | | 8b+10b+2+3b= | | s=6r^3(s/6r^3) | | -10+6x=3x-4 | | X/48=5/6 | | 7x+5=-5x |

Equations solver categories